Heterojunction-porous composite material and microwave sensitizer

By using a heterojunction-porous composite material combining bimetallic oxides and a carbon layer substrate, the problems of poor controllability of ablation range and difficulty in tumor boundary identification in microwave ablation therapy have been solved. This enables precise ablation of tumors and enhanced microwave sensitization, and is applicable to microwave, photodynamic, and sonodynamic therapy.

CN119280421APending Publication Date: 2025-01-10NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411179417.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Current microwave ablation therapy suffers from problems such as poor controllability of ablation range, difficulty in identifying tumor boundaries, and poor sensitization effect of microwave sensitizers, especially at the tumor margins where the treatment effect is unsatisfactory. Furthermore, the microwave thermal conversion performance and reactive oxygen species yield of existing sensitizer materials are insufficient.

Method used

A heterojunction-porous composite material combining bimetallic oxide and carbon layer substrate is used to enhance microwave absorption performance and electron-hole separation efficiency by constructing a heterojunction structure. Combined with the ion collision confinement effect of the porous structure, the microwave thermal sensitization effect is improved. Furthermore, the yield of reactive oxygen species is enhanced by the catalytic generation of oxygen from hydrogen peroxide by variable valence metal ions in the material.

Benefits of technology

It achieves improved controllability of microwave ablation range, precise identification of tumor boundaries, and enhanced microwave sensitization effect, thereby improving the efficacy of tumor treatment and enhancing reactive oxygen species production in photodynamic and sonodynamic therapy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280421A_ABST
    Figure CN119280421A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microwave sensitizers, and relates to a heterojunction-porous composite material and a microwave sensitizer. The invention discloses a bimetallic oxide and carbon layer substrate compounded heterojunction-porous composite material. The bimetallic oxide and carbon layer substrate compounded heterojunction-porous composite material is prepared by carbonizing a porous bimetallic-organic framework material in a protective atmosphere at 400-900 DEG C, the porous bimetal-organic framework material is an X metal ion doped Y metal-organic framework material, X metal and Y metal both comprise one or more of rare earth metal, alkaline earth metal, main group metal and transition element metal, and the X metal and the Y metal are different metals. According to the invention, the composition and doping ratio of the X and Y metals are adjusted, the structure morphology of the heterojunction-porous composite material compounded by the bimetallic oxide and the carbon layer substrate is adjusted, and the formation of the heterojunction structure is regulated, so that the heterojunction-porous composite material has good microwave thermal sensitization performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave sensitizers and relates to a heterojunction-porous composite material and a microwave sensitizer. Background Art

[0002] Microwave ablation (MWA) is a minimally invasive tumor interventional treatment technology. Under the guidance of imaging technology, the microwave ablation needle is directly inserted into the tumor site. The electromagnetic waves emitted by the microwave needle cause the polar molecules in the tissue to generate heat through high-speed friction, thereby achieving ablation of the lesion tissue. Due to the difference in dielectric constants between tumor tissue and normal tissue, thermal ablation has little effect on normal tissue. Compared with traditional treatment methods, microwave ablation has the advantages of minimal invasiveness, fewer complications, and high safety. Currently, MWA has achieved certain results in the treatment of tumors in the liver, uterus, prostate, and kidneys. However, in the clinical application of MWA, there are still a series of key issues that need to be solved. (1) Ablation range: The temperature field of microwave ablation surrounds the microwave ablation needle and decreases with increasing distance, which results in poor controllability of the microwave ablation range. The tumor boundary may not reach the temperature required for ablation, which in turn leads to tumor recurrence. Although the tumor ablation range can be expanded to a certain extent by increasing the MWA power and extending the ablation time, the high-temperature carbonization of cancerous tissue near the microwave needle reduces the efficiency of temperature conduction to the tumor edge, and the MWA has poor efficacy on the tumor edge. (2) Tumor boundary identification and ablation status monitoring: Microwave ablation requires the guidance of medical imaging technology in clinical application, such as magnetic resonance imaging (MRI), computed tomography (CT) and ultrasound imaging. These imaging technologies are difficult to accurately locate the ablated necrotic tissue when used. Therefore, microwave ablation of tumors cannot accurately judge and identify the boundaries of the tumor and its surrounding normal tissue structures, resulting in incomplete tumor ablation or damage to surrounding normal tissues. Microwave sensitizers have unique advantages in solving the above problems.

[0003] Microwave sensitizers refer to materials that can improve the effect of microwave ablation treatment of tumors. Microwave sensitization can be divided into microwave thermal sensitization and microwave dynamic sensitization according to different principles. Microwave thermal sensitization is to increase the concentration of polar molecules or the collision efficiency of polar molecules through microwave sensitizers, and convert kinetic energy into thermal energy. Commonly used ionic liquids (IL) are usually encapsulated by liposomes, metal-organic frameworks (MOFs), etc., to enhance the concentration of polar molecules in the tumor area, thereby rapidly increasing the temperature of tumor tissue; MOF and porous materials use their porous structures to enhance the collision efficiency of polar molecules in the pores and thus improve the thermal conversion efficiency. Microwave dynamic sensitization is that microwave sensitizers (such as titanium dioxide, liquid metal, etc.) are excited by microwave irradiation, and free electrons and holes are separated, inducing oxygen or hydrogen peroxide in the tumor microenvironment to produce singlet oxygen, hydroxyl free radicals and other reactive oxygen species, which then undergo oxidation reactions with tumor cells and induce apoptosis or necrosis.

[0004] The existing thermal sensitization methods of microwave ablation sensitizers mainly achieve thermal sensitization by enhancing the ion collision efficiency in confined spaces through pore confinement, encapsulation of ionic liquids, etc., and do not pay attention to the microwave thermal conversion performance caused by the microwave absorption of the sensitizer material itself; microwave dynamic sensitization focuses on microwave excitation of electron-hole separation of sensitizers, and then produces reactive oxygen species to achieve microwave dynamic sensitization. However, because microwave thermal sensitization is difficult to break through the principle of ion collision efficiency, microwave dynamic sensitization is difficult to overcome the bottleneck of low reactive oxygen species yield caused by hypoxia in tumor tissues, resulting in a single sensitization principle for current microwave sensitizers and poor sensitization effects. Therefore, there is an urgent need to break through the existing microwave thermal sensitization and reactive oxygen sensitization principles, and develop heterojunction-porous composite structure sensitizer materials with high microwave absorption and self-oxygen production performance. Summary of the invention

[0005] The purpose of the present invention is to propose a heterojunction-porous structure sensitizer material with microwave absorption performance in view of the above-mentioned problems existing in the prior art, and to improve the microwave thermal sensitization effect by combining the high microwave absorption performance of the material with the ion collision confinement effect of the porous structure; to improve the electron-hole separation efficiency of the material under microwave excitation by the heterojunction, and to catalyze the hydrogen peroxide in the tumor microenvironment to produce oxygen by combining the Fenton-like reaction activity of the variable-valence metal ions in the material, thereby increasing the yield of reactive oxygen species, that is, improving the microwave dynamic sensitization effect.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate, wherein the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate is prepared by carbonizing a porous bimetallic-organic framework material at 400-900° C. in a protective atmosphere;

[0008] The porous bimetallic-organic framework material is an X metal ion doped Y metal-organic framework material, wherein the X metal and the Y metal both include one or more of rare earth metals, alkaline earth metals, main group metals, and transition element metals, and the X metal and the Y metal are different metals.

[0009] Preferably, the carbonization temperature is 500-700° C., and the carbonization time is 1-12 hours.

[0010] Preferably, the porous bimetallic-organic framework material is prepared by adding ligand molecules and Y metal compounds to a mixed organic solution, reacting at 50-130° C. for 1-24 hours, adding X metal doping salt, and reacting at 135-200° C. for 12-48 hours.

[0011] Further preferably, the porous bimetallic-organic framework material is prepared by adding ligand molecules and Y metal compounds to a mixed organic solution, reacting at 60-90° C. for 6-24 hours, adding X metal doping salt, and reacting at 140-170° C. for 12-36 hours.

[0012] Preferably, the porous bimetallic-organic framework material is in the form of nanosheets with an average size of 100 to 1000 nm and a thickness of 10 to 50 nm.

[0013] More preferably, the average size of the porous bimetallic-organic framework material is 200-500 nm.

[0014] Preferably, the rare earth metal includes one or more of Ce, Er, and Yb, the alkaline earth metal includes one or two of Mg and Ca, the main group metal includes one or more of Al, Ga, Ge, In, and Sn, and the transition element metal includes one or more of Zn, Cu, Ni, Co, Fe, Mn, Cr, V, Ti, Sc, Cd, Ag, Ru, Zr, Mo, Nb, Zr, Pt, Ir, Os, and Hf.

[0015] Preferably, the ligand molecules include: porphyrin ligands, carboxylic acid ligands, phthalic acid, terephthalic acid, phthalic acid, 1,4-phthalic acid, p-hydroxybenzoic acid, pyridine and its derivatives, 1,4-benzenedicarboxylic acid, trimesic acid, tetrasic acid, benzodicarboxylic acid, benzohexacarboxylic acid, 1,3,5-tricarboxylic acid benzene, aminoacetic acid, lysine, valine, phenylglycine, phenylalanine, phenylalanine, aromatic diol ligands, non-aromatic diol ligands, and aromatic diamine ligands.

[0016] Preferably, the Y metal compound includes one or more of transition element metal salts, main group metal salts, rare earth metal salts, alkaline earth metal salts, and transition element metal oxide clusters.

[0017] Further preferably, the Y metal compound includes one or more of magnesium nitrate, aluminum nitrate, scandium nitrate, tetrabutyl titanate, titanium tetrachloride, titanium trichloride, titanium isopropoxide, vanadium nitrate, chromium nitrate, manganese nitrate, iron chloride, cobalt nitrate, nickel nitrate, copper nitrate, zinc nitrate, hydrated gallium nitrate, germanium oxide, zirconium chloride, niobium (IV) chloride tetrahydrofuran complex, molybdenum trioxide, ruthenium chloride, silver nitrate, cadmium acetate, stannous chloride, cerium ammonium nitrate, hafnium tetrachloride, ytterbium nitrate, triosmium dodecacarbonyl, iridium chloride, Zr6O8 metal cluster, copper oxide metal cluster, and hexameric titanium oxide cluster.

[0018] Preferably, the X metal doping salt includes one or more of transition element metal salts, main group metal salts, rare earth metal salts, and alkaline earth metal salts.

[0019] Further preferably, the X metal doping salt includes one of magnesium nitrate, aluminum nitrate, tetrabutyl titanate, vanadium nitrate, chromium trichloride, manganese chloride tetrahydrate, iron (III) nitrate nonahydrate, cobalt nitrate hexahydrate, cobalt chloride, nickel (II) nitrate hexahydrate, copper (II) nitrate trihydrate, zinc nitrate, hydrated gallium nitrate, zirconium chloride, (tert-butylimino) tris (diethylamido) niobium (V), molybdenum trioxide, ruthenium chloride, cadmium nitrate, stannous chloride, platinum dichloride, platinum tetrachloride, cerium nitrate hexahydrate, hafnium tetrachloride, ytterbium nitrate, and iridium chloride.

[0020] Preferably, the Y metal is an early transition metal, including one or more of Cr, V, Ti, Sc, Zr, Mo, Nb, and Hf;

[0021] The X metal is a late transition metal, including one or more of Zn, Cu, Ni, Co, Fe, Cd, Mn, Cd, Ag, Ru, Pt, Ir, and Os.

[0022] Preferably, the molar ratio of X metal doping salt:Y metal compound in the porous bimetallic-organic framework material is 1:(0.1-10).

[0023] More preferably, the molar ratio of X metal doping salt:Y metal compound in the porous bimetallic-organic framework material is 1:(0.25-4).

[0024] Preferably, the mixed organic solution is a mixture of N,N-dimethylformamide and methanol.

[0025] A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate is CoO / TiO2@C, which is prepared by carbonizing a porous bimetallic-organic framework material Co / Ti MOFs at 400-900°C in an inert gas.

[0026] The heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate of the present invention has a heterojunction structure. The construction of the heterojunction structure realizes the polarization effect to enhance the electron flow, is beneficial to the separation transition of electron pairs, and enhances the microwave power performance and increases the active oxygen yield.

[0027] Preferably, the preparation method of the porous bimetallic-organic framework material Co / Ti MOFs comprises: adding ligand molecules and Ti metal compounds to a mixed organic solution, reacting at 50-130°C for 1-24 hours, adding Co metal doping salt, and reacting at 135-200°C for 12-48 hours to obtain the obtained material.

[0028] The present invention introduces cobalt oxide into a heterojunction-porous composite material of a double metal oxide and a carbon layer substrate and constructs a heterojunction, thereby improving the microwave absorption performance of the material itself and further improving the microwave thermal effect.

[0029] A heterojunction-porous composite material of a double metal oxide and a carbon layer substrate composited with a surface-modified polymer, wherein a polymer is modified on the surface of the heterojunction-porous composite material of the double metal oxide and the carbon layer substrate composited with the surface.

[0030] Preferably, the preparation method of the heterojunction-porous composite material of the bimetallic oxide of the surface modified polymer and the carbon layer substrate comprises: dispersing the heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate, stirring and reacting with the polymer for 1 to 48 hours, and after the reaction, centrifuging to obtain the heterojunction-porous composite material of the bimetallic oxide of the surface modified polymer and the carbon layer substrate.

[0031] Preferably, the polymer includes: chitosan, soluble pectin, plant polysaccharide compounds, maltodextrin, amino polyethylene glycol, carboxyl polyethylene glycol, phospholipid polyethylene glycol carboxyl, dextran, carboxymethyl dextran, carboxymethyl chitosan, carboxymethyl starch, polyacrylic acid, polystyrene-b-polyacrylic acid, polymaleic acid, polylactic acid, polylactic acid-glycolic acid, polypyrrolidone, polysorbate, polylactide, polycaprolactone, polyglycolic acid, polyamino acid, polyacrylic acid, polymethacrylic acid, polylactic acid, polyglycolic acid, lactic acid-glycolic acid copolymer, polyoxyethylene polyoxypropylene ether block copolymer, carbomer copolymer, glycolide-lactide copolymer, lauroyl polyoxyethylene glyceride, ethyl acrylate-methyl methacrylate copolymer, polyethylene glycol-distearoyl phosphatidylethanolamine, polydopamine, polyethyleneimine, polyethyleneamine, liposomes, albumin nanospheres and one or more thereof.

[0032] A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate coupled with tumor targeting molecules, wherein tumor targeting molecules are coupled on the surface of the heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate and / or the heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate with a surface modified polymer.

[0033] Preferably, the tumor targeting molecule comprises one or more of folic acid, RGD peptide (arginyl-glycyl-aspartic acid), vascular endothelial growth factor, neuropeptide, tumor-specific antibody or polypeptide.

[0034] A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with antitumor drugs, wherein the antitumor drugs are loaded on the surface of the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate, and / or the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate with a surface modified polymer, and / or the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate coupled with a tumor targeting molecule.

[0035] Preferably, the anti-tumor drugs include one or more of doxorubicin, paclitaxel and cisplatin.

[0036] A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with an immune activator, wherein the immune activator is loaded on the surface of a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate, and / or a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate with a surface modified polymer, and / or a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate coupled with a tumor targeting molecule, and / or a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with an anti-tumor drug.

[0037] Preferably, the immune activator is R848.

[0038] A microwave sensitizer comprises one or more of a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate, a heterojunction-porous composite material of a bimetallic oxide with a surface-modified polymer and a carbon layer substrate, a heterojunction-porous composite material of a bimetallic oxide coupled with a tumor targeting molecule and a carbon layer substrate, a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with an anti-tumor drug, and a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with an immune activator.

[0039] Preferably, in a heterojunction-porous composite material solution of a double metal oxide of a surface-modified polymer and a carbon layer substrate with a concentration of 0 to 100 μg / mL, the survival rate of HepG2 cells and L-02 cells is ≥85%.

[0040] Preferably, in a CoO / TiO2@C@PEG solution with a concentration of 0 to 100 μg / mL, the survival rate of HepG2 cells and L-02 cells is ≥85%.

[0041] Preferably, in a heterojunction-porous composite material composed of a double metal oxide of a surface-modified polymer and a carbon layer substrate with a concentration of 0 to 100 μg / mL + 100 μM H2O2 solution, after incubation with HepG2 cells for 3 hours, microwave irradiation was performed with an output power of 2 W and an irradiation time of 5 minutes, and the survival rate of HepG2 cells was as low as 28.6%.

[0042] Preferably, after incubating HepG2 cells in a CoO / TiO2@C@PEG+100 μM H2O2 solution with a concentration of 0-100 μg / mL for 3 h, microwave irradiation was performed with an output power of 2 W and an irradiation time of 5 min, and the survival rate of HepG2 cells was as low as 28.6%.

[0043] Preferably, the heterojunction-porous composite material composed of a double metal oxide of a surface-modified polymer and a carbon layer substrate + H2O2 is co-incubated with HepG2 cells and then subjected to microwave irradiation, with an output power of 2W and an irradiation time of 5min. ROS increases significantly at the cellular level, and the green fluorescence on the cells is significantly enhanced at an excitation wavelength of 488nm.

[0044] Preferably, CoO / TiO2@C@PEG+H2O2 was co-incubated with HepG2 cells and then subjected to microwave irradiation with an output power of 2 W and an irradiation time of 5 min. ROS increased significantly at the cellular level, and the green fluorescence on the cells was significantly enhanced at an excitation wavelength of 488 nm.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention adjusts the composition and doping ratio of X and Y metals, adjusts the structural morphology of the heterojunction-porous composite material of the double metal oxide and the carbon layer substrate, and regulates the formation of the heterojunction structure, so that it has good microwave thermal sensitization performance.

[0047] 2. The present invention performs annealing and carbonization treatment on the porous bimetallic-organic framework material to obtain a heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate while retaining the porous characteristics of the metal-organic framework. This can well achieve pore confinement and enhance the microwave thermal performance of the material. At the same time, the carbonized composite material can well reduce the band gap of the material, facilitate the separation and transition of electron-hole pairs, and enhance the microwave power performance, thereby achieving synergistic enhancement of microwave heat and microwave power.

[0048] 3. In the heterojunction-porous composite material of the double metal oxide and the carbon layer substrate of the heterojunction structure of the present invention, due to the difference in electronegativity between the two metal oxides, charge transfer and polarization effects will occur, resulting in the flow of electrons, which is beneficial to the separation transition of charges and enhances the microwave power sensitization performance.

[0049] 4. The heterojunction-porous composite material of the double metal oxide and the carbon layer substrate of the present invention includes a metal oxide with good low-frequency resonance and eddy current loss capabilities. The good magnetic loss capability of the metal oxide is utilized to adjust the impedance matching of the material and enhance the magnetic loss capability of the material in the medical microwave frequency band, thereby constructing a microwave therapy sensitizer with enhanced low-frequency microwave absorption.

[0050] 5. The present invention significantly enhances the microwave absorption performance of the material through metal doping and annealing carbonization, and the absorption rate reaches 96.6% in the 2.45 GHz band.

[0051] 6. The microwave sensitizer of the present invention can also effectively increase the yield of active oxygen during photodynamic therapy and sonodynamic therapy, and can also be used for sensitization applications in tumor photodynamic therapy and sonodynamic therapy. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a TEM image of the bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:4) in Example 1 of the present invention.

[0053] Figure 2 This is a TEM image of the bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:2) in Example 2 of the present invention.

[0054] Figure 3 This is a TEM image of the bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:1) in Example 3 of the present invention.

[0055] Figure 4 This is a TEM image of the bimetallic-organic framework material Co-Ti MOFs (Co:Ti=2:1) ​​in Example 4 of the present invention.

[0056] Figure 5 This is a TEM image of the bimetallic-organic framework material Co-Ti MOFs (Co:Ti=4:1) in Example 5 of the present invention.

[0057] Figure 6 (a~e) are TEM images of the heterojunction-porous composite materials CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) of the bimetallic oxide and carbon layer substrate in Examples 9~13 of the present invention.

[0058] Figure 7 This is a TEM image of the metal-organic framework material Ti MOFs in Comparative Example 1 of the present invention.

[0059] Figure 8 This is a TEM image of the single metal oxide and carbon layer substrate composite material TiO2@C in Comparative Example 2 of the present invention.

[0060] Fig. 9 This is a TEM image of the metal-organic framework material Co MOFs in Comparative Example 3 of the present invention.

[0061] Fig.10 This is a TEM image of the single metal oxide and carbon layer substrate composite material CoO@C in Comparative Example 4 of the present invention.

[0062] Fig.11 The Tauc curves are those of Co-Ti MOFs (Co:Ti=4:1) in Example 5 and CoO / TiO2@C (Co:Ti=4:1) in Example 13 of the present invention.

[0063] Fig.12 The adsorption / desorption curve (a) and the pore distribution diagram of the desorption curve (b) of the metal-organic framework material Ti MOFs in comparative example 1 of the present invention, the adsorption / desorption curve (c) and the pore distribution diagram of the desorption curve (d) of the heterojunction-porous composite material CoO / TiO2@C (Co:Ti=1:4) composited with a double metal oxide and a carbon layer substrate in Example 9.

[0064] Fig.13 (a) XPS full spectrum, (b) O 1s high-resolution XPS spectrum, (c) Co 2p high-resolution XPS spectrum, and (d) Ti 2p high-resolution XPS spectrum of the heterojunction-porous composite material CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) of the bimetallic oxide and carbon layer substrate in Examples 9 to 13 of the present invention.

[0065] Fig.14 This is a reflection loss diagram of each band of the heterojunction-porous composite material CoO / TiO2@C (Co:Ti=4:1) composed of a double metal oxide and a carbon layer substrate in Example 13 of the present invention.

[0066] Fig.15The temperature rise curves (a) of Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 1 to 5 of the present invention, Ti MOFs in Comparative Example 1, and Co MOFs in Comparative Example 3 under 2W microwave irradiation, and the temperature rise curves (b) of CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 9 to 13, TiO2@C in Comparative Example 2, and CoO@C in Comparative Example 4 under 2W microwave irradiation.

[0067] Fig.16 The temperature rise curves (a) of Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) + H2O2 in Examples 1 to 5 of the present invention, Ti MOFs + H2O2 in Comparative Example 1, and Co MOFs + H2O2 in Comparative Example 3 under 2W microwave irradiation, and the temperature rise curves (b) of CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) + H2O2 in Examples 9 to 13, TiO2@C + H2O2 in Comparative Example 2, and CoO@C + H2O2 in Comparative Example 4 under 2W microwave irradiation.

[0068] Fig.17 This is the ultraviolet absorption spectrum of Co-Ti MOFs (Co:Ti=1:4)+H2O2 under 2W microwave irradiation for different times in Example 1 of the present invention (a), and the ultraviolet absorption spectrum of CoO / TiO2@C (Co:Ti=4:1)+H2O2 under 2W microwave irradiation for different times in Example 13 (b).

[0069] Fig.18 This is a microwave dynamic sensitization performance diagram comparing Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) + H2O2 in Examples 1 to 5 of the present invention, Ti MOFs + H2O2 in Comparative Example 1, and Co MOFs + H2O2 in Comparative Example 3 using DPBF.

[0070] Fig.19 This is a microwave dynamic sensitization performance diagram comparing CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) + H2O2 in Examples 9 to 13 of the present invention, TiO2@C + H2O2 in Comparative Example 2, and CoO@C + H2O2 in Comparative Example 4 using DPBF.

[0071] Fig. 20 Fluorescence images of CoO / TiO2@C@PEG and HepG2 cells after culturing for 0, 0.5, 2, 3, and 4 hours in Example 3 of the present invention

[0072] Fig.21This is a graph showing the cell survival rate results of Co-Ti MOFs@PEG, CoO / TiO2@C@PEG, CoO / TiO2@C@PEG+100μM H2O2 and L-02 cells (a) and HepG2 cells (b) after being cultured for 2 hours at different experimental concentrations in Application Example 3 of the present invention.

[0073] Fig. 22 This is a graph showing the cell survival results after Co-Ti MOFs@PEG, CoO / TiO2@C@PEG, and CoO / TiO2@C@PEG+100μM H2O2 in Application Example 4 of the present invention were incubated with HepG2 cells at different concentrations and subjected to microwave treatment.

[0074] Fig.23 These are fluorescence images generated by Co-Ti MOFs@PEG, Co-Ti MOFs@PEG+H2O2, CoO / TiO2@C@PEG, and CoO / TiO2@C@PEG+H2O2 in Application Example 5 of the present invention for HepG2 cells co-incubated and stained with ROS probe with / without microwave treatment. DETAILED DESCRIPTION

[0075] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0076] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.

[0077] Example 1

[0078] Weigh 543 mg of p-hydroxybenzoic acid and 205 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 43.65 mg of cobalt nitrate hexahydrate (Co:Ti feed ratio is 1:4) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:4).

[0079] Example 2

[0080] Weigh 543 mg of p-hydroxybenzoic acid and 171 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 72.75 mg of cobalt nitrate hexahydrate (Co:Ti feed ratio is 1:2) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:2).

[0081] Example 3

[0082] Weigh 543 mg of p-hydroxybenzoic acid and 130 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 109.14 mg of cobalt nitrate hexahydrate (Co:Ti feed ratio is 1:1) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:1).

[0083] Example 4

[0084] Weigh 543 mg of p-hydroxybenzoic acid and 85 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 145.52 mg of cobalt nitrate hexahydrate (Co:Ti feed ratio is 2:1) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=2:1).

[0085] Example 5

[0086] Weigh 543 mg of p-hydroxybenzoic acid and 52 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 174.62 mg of cobalt nitrate hexahydrate (Co:Ti feed ratio is 4:1) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=4:1).

[0087] Example 6

[0088] Weigh 543 mg of aminoacetic acid and 48 mg of hexameric titanium oxide clusters, dissolve them in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve them at room temperature for 30 minutes, and stir them at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 60°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 220 mg of cobalt chloride (Co:Ti feed ratio is 1:4) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 140°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ti MOFs (Co:Ti=1:4).

[0089] Example 7

[0090] Weigh 543 mg of phenylalanine and 116.24 mg of nickel nitrate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 90°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 23.79 mg of cobalt chloride (Co:Ni feed ratio is 1:4) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 170°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Co-Ni MOFs (Co:Ni=1:4).

[0091] Example 8

[0092] Weigh 543 mg of pyridine and 75.84 mg of titanium tetrachloride, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add 18.94 mg of zinc nitrate (Zn:Ti feed ratio is 1:4) to the above reaction suspension and mix well. Transfer the mixed solution precursor to a high-pressure reactor and react at 150°C for 24 hours. After the reaction is completed, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous bimetallic-organic framework material Zn-Ti MOFs (Zn:Ti=1:4).

[0093] Examples 9 to 13

[0094] Take 500 mg of the porous bimetallic-organic framework Co-Ti MOFs powder in Examples 1 to 5, place the powder in a tube furnace, and heat the reaction at 600°C for 2 hours under argon protection. After the reaction, disperse the mixed powder into anhydrous ethanol, centrifuge at 12,000 rpm for 30 minutes, repeat 3 times, and then disperse into deionized water, centrifuge at 12,000 rpm for 30 minutes, dry the obtained reactant, and obtain a heterojunction-porous composite material CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) of a bimetallic oxide and a carbon layer substrate.

[0095] Embodiment 14

[0096] Take 15 mg of the porous bimetallic-organic framework material Co-Ti MOFs powder in Examples 1 to 5, disperse it in 20 ml of deionized water, and dissolve it with ultrasonic for 1 hour. Then add 10 mg of polyethylene glycol to the solution and continue stirring the reaction for 24 hours. After the reaction is completed, the reactant is centrifuged at 12,000 rpm for 30 minutes to obtain a polyethylene glycol-modified bimetallic-organic framework composite material Co-Ti MOFs@PEG.

[0097] Embodiment 15

[0098] Take 15 mg of the CoO / TiO2@C powder of the heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate in Examples 9 to 13, disperse it in 20 ml of deionized water, and dissolve it with ultrasonic for 1 hour. Then add 10 mg of polyethylene glycol to the solution and continue stirring the reaction for 24 hours. After the reaction is completed, the reactant is centrifuged at 12000 rpm for 30 minutes to obtain the polyethylene glycol-modified bimetallic oxide and the carbon layer substrate heterojunction-porous composite material CoO / TiO2@C@PEG.

[0099] Example 16

[0100] Take 100 mg of the Co-Ti MOFs@PEG powder in Example 14, disperse it in a buffer solution of pH 7.5, add 10 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 5 mg of N-hydroxysulfosuccinimide, stir to activate the carboxyl group for 1 hour, add 5 mg of RGD short peptide, and stir to react for 16 hours. After the reaction is completed, centrifuge at 12000 rpm for 30 minutes to remove excess reactants, and obtain the RGD short peptide-coupled bimetallic-organic framework composite material Co-Ti MOFs@PEG@RGD.

[0101] Embodiment 17

[0102] Take 100 mg of CoO / TiO2@C@PEG powder in Example 15, disperse it in a buffer solution of pH 7.5, add 10 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 5 mg of N-hydroxysulfosuccinimide, stir to activate the carboxyl group for 1 hour, add 5 mg of RGD short peptide, and stir to react for 16 hours. After the reaction is completed, centrifuge at 12000 rpm for 30 minutes to remove excess reactants to obtain a heterojunction-porous composite material CoO / TiO2@C@PEG@RGD of a bimetallic oxide coupled with an RGD short peptide and a carbon layer substrate.

[0103] Embodiment 18

[0104] Take 100 mg of the RGD short peptide coupled bimetallic oxide and carbon layer substrate composite heterojunction-porous composite material CoO / TiO2@C@PEG@RGD powder in Example 17, disperse it in a pH 7.5 buffer solution, add 10 mg of doxorubicin, and stir to react for 24 hours in a dark place. After the reaction is completed, centrifuge at 12000 rpm for 30 minutes to remove excess reactants to obtain a heterojunction-porous composite material CoO / TiO2@C@PEG@RGD@ADM loaded with doxorubicin and a bimetallic oxide and a carbon layer substrate.

[0105] Embodiment 19

[0106] Take 100 mg of the ADM-RGD-PEG-CoO / TiO2@C powder of the bimetallic oxide loaded with doxorubicin and the carbon layer substrate, dispersed in a pH 7.5 buffer solution, add 10 mg of the immune activator R848, and stir to react for 24 hours. After the reaction is completed, centrifuge at 12000 rpm for 30 minutes to remove excess reactants to obtain the heterojunction-porous composite material CoO / TiO2@C@PEG@RGD@ADM@R848 of the bimetallic oxide loaded with the immune activator R848 and the carbon layer substrate.

[0107] Comparative Example 1

[0108] Weigh 543 mg of p-hydroxybenzoic acid and 260 mg of tetrabutyl titanate, dissolve in a mixed solution of 13.5 ml of N,N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction, cool the reactor to room temperature, wash it three times with N,N-dimethylformamide and methanol respectively, and dry the sample to obtain the metal-organic framework material Ti MOFs.

[0109] Comparative Example 2

[0110] Take 500 mg of the metal-organic framework material Ti MOFs powder in Comparative Example 1, place the powder in a tube furnace, and heat the reaction at 600°C for 2 hours under argon protection. After the reaction, disperse the mixed powder into anhydrous ethanol, centrifuge at 12,000 rpm for 30 minutes, repeat 3 times, and then disperse into deionized water, centrifuge at 12,000 rpm for 30 minutes, and dry the obtained reactant to obtain a single metal oxide and carbon layer substrate composite material TiO2@C.

[0111] Comparative Example 3

[0112] Weigh 543 mg of p-hydroxybenzoic acid and 218.28 mg of cobalt nitrate hexahydrate, dissolve in a mixed solution of 13.5 ml of N, N-dimethylformamide and 1.5 ml of methanol, ultrasonically dissolve for 30 minutes at room temperature, and stir at 1000 rpm for 1 hour. Transfer the solution to a high-temperature reactor and react at 80°C for 12 hours. After the reaction, wait for the reactor to cool to room temperature, wash it three times with N, N-dimethylformamide and methanol respectively, and dry the sample to obtain a porous single metal-organic framework material Co MOFs.

[0113] Comparative Example 4

[0114] Take 500 mg of the metal-organic framework material Co MOFs powder in Comparative Example 3, place the powder in a tube furnace, and heat the reaction at 600°C for 2 hours under argon protection. After the reaction, disperse the mixed powder into anhydrous ethanol, centrifuge at 12000 rpm for 30 minutes, repeat 3 times, and then disperse it into deionized water, centrifuge at 12000 rpm for 30 minutes, and dry the obtained reactant to obtain a single metal oxide and carbon layer substrate composite material CoO@C.

[0115] Application Example 1

[0116] The materials prepared above were characterized.

[0117] (1) Based on Figures 1 to 5 , 7, 8 show that, Figure 7 The Ti MOFs are shown in the figure to be square flake-shaped. With the doping of metallic cobalt, the Co-Ti MOFs (Co:Ti=1:4, 1:2) present a nano-disk-shaped morphology. With the further increase of the cobalt doping amount, the morphology of Co-Ti MOFs (Co:Ti=1:1, 2:1, 4:1) tends to be Figure 8 The polygonal flake morphology of Co MOFs gradually evolves.

[0118] according to Figure 6 , 9 , 10, it can be seen that CoO@C presents a nano-disk morphology of single metal particles aggregated, and TiO2@C presents a rectangular flake morphology with high contrast; with the increase of Co doping amount, CoO particles aggregate from the uniform MOF to form a heterojunction structure.

[0119] The doping content of CoO / TiO2@C with different Co:Ti feed ratios in Examples 9 to 13 was analyzed by ICP, and the results are shown in Table 1 below:

[0120] Table 1. Analysis of doping molar percentage of CoO / TiO2@C with different Co:Ti feed ratios

[0121] Feed ratio Co doping molar percentage Ti doping molar percentage Example 9 1:4 2.7% 11.2% Example 10 1;2 4.6% 9.4% Embodiment 11 1:1 6.8% 7.1% Example 12 2:1 9.7% 4.9% Example 13 4:1 12.1% 2.9%

[0122] According to the above table, the molar percentages of the cobalt and titanium elements in the obtained products are close to the reaction feed ratio; the influence of the doping ratio on the performance can be studied by quantification according to the feed ratio.

[0123] (2) The Tauc curves of Co-Ti MOFs (Co:Ti=4:1) and CoO / TiO2@C (Co:Ti=4:1) were calculated by using the Kubelka-MunK (KM) function. Fig.11 The band gap of the original Co-Ti MOFs is 2.391eV, while the band gap of the annealed CoO / TiO2@C is about 1.383eV. CoO / TiO2@C has a smaller band gap than the original Co / Ti MOFs. The reduced band gap is more conducive to the separation of electron-hole pairs induced by microwave excitation, promoting the excitation of electrons from VB to CB, and is conducive to the generation of ROS.

[0124] (3) Based on Fig.12 From the adsorption-desorption curve and the pore distribution diagram of the desorption curve, it can be seen that CoO / TiO2@C (Co:Ti=4:1) in Example 13 still maintains the porous structure of Ti MOFs, and can enhance the microwave thermal performance through pore confinement to achieve efficient microwave thermal sensitization.

[0125] (4) Full XPS spectra and single atom XPS spectra of CoO / TiO2@C with different Co:Ti feed ratios Fig.13 It can be seen that with the increase of Co:Ti feed ratio, the vacancy oxygen in the system increases, and with the gradual increase of the amount of Co doping, the ratio of vacancy oxygen / lattice oxygen also increases, which proves that Co doping leads to the presence of abundant oxygen defects in the material. These defects can capture electrons and improve the electron-hole separation efficiency.

[0126] (5) The microwave absorption performance of CoO / TiO2@C (Co:Ti=4:1) in Example 13 was characterized by a vector network analyzer. The reflection loss diagram of each band is shown in FIG. Fig.14 As shown, its microwave absorption reflection loss in the medical treatment band of 2.45 GHz is the lowest, which is -22.68 dB (absorption rate is 96.6%); this proves that the prepared material has good low-frequency microwave absorption performance, laying the foundation for achieving efficient microwave absorption in the medical frequency band.

[0127] Application Example 2

[0128] (1) In vitro microwave sensitization performance test 1:

[0129] Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 1 to 5, TiMOFs in Comparative Example 1, Co MOFs in Comparative Example 3, CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 9 to 13, TiO2@C in Comparative Example 2, and CoO@C in Comparative Example 4 were dispersed in 0.9% NaCl to obtain a homogeneous solution with a concentration of 100 μg / mL as an experimental group. A separate 0.9% NaCl group was set as a control group.

[0130] The microwave probe was vertically inserted into a cuvette containing 1 mL of liquid, and the microwave output power was 2 W for 5 min.

[0131] according to Fig.15It can be seen that in the 0.9% NaCl group (control group), the solution temperature increased by 12.15°C after 5 minutes of microwave irradiation. Compared with the control group, the solution temperature of the experimental group increased more significantly after 5 minutes of microwave irradiation, proving that CoMOFs, Ti MOFs, Co-Ti MOFs and CoO / TiO2@C all have microwave thermal sensitization. Among them, the solution temperature of the Co-Ti MOFs (Co:Ti=1:1) group increased by 22.51°C after 5 minutes of microwave irradiation, and the solution temperature of the CoO / TiO2@C (Co:Ti=1:1, 2:1, 4:1) group increased by 29.22, 27.09, and 28.55°C after 5 minutes of microwave irradiation, respectively. The temperature of the Co-Ti MOFs (Co:Ti=1:1) group and the CoO / TiO2@C (Co:Ti=1:1) group increased by 10.36℃ and 17.07℃ respectively compared with the 0.9% NaCl group. The results show that Co-Ti MOFs and CoO / TiO2@C with appropriate doping ratios have excellent microwave thermal sensitization. The increase in temperature is due to the large pores and porosity of MOFs. When MOFs are dispersed in 0.9% NaCl solution, a large number of ions are easily enriched in the pores of MOFs. Under microwave irradiation, the ions confined in the mesoporous structure undergo high-frequency inelastic collisions, converting kinetic energy into heat, resulting in a significant increase in temperature, thus having microwave thermal sensitivity. At the same time, it can be observed that the microwave thermal performance of CoO / TiO2@C after annealing and carbonization is improved to a certain extent compared with Co-Ti MOFs, which can be attributed to the increase in porosity and enhanced microwave absorption after annealing. The above results indicate that the CoO / TiO2@C prepared in the present invention is an effective microwave thermal sensitizer under low-power microwaves.

[0132] (2) In vitro microwave sensitization performance test 2:

[0133] Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 1 to 5, TiMOFs in Comparative Example 1, Co MOFs in Comparative Example 3, CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 9 to 13, TiO2@C in Comparative Example 2, and CoO@C in Comparative Example 4 were dispersed in 0.9% NaCl to obtain a homogeneous solution with a concentration of 100 μg / mL as the experimental group. A separate 0.9% NaCl group was set as the control group. H2O2 was added to both the experimental group and the control group and quantified to 100 μM.

[0134] The microwave probe was vertically inserted into a cuvette containing 1 mL of liquid, and the microwave output power was 2 W for 5 min.

[0135] according to Fig.16 It can be seen that compared with the group without H2O2, the microwave thermal performance is improved after adding H2O2. After 5 minutes of microwave irradiation, the solution temperature of the Co-Ti MOFs (Co:Ti=1:1) group increased by 24.23℃, and the solution temperature of the CoO / TiO2@C (Co:Ti=1:1, 2:1, 4:1) group increased by 31.42, 29.57, and 30.12℃ respectively after 5 minutes of microwave irradiation. The results show that the addition of H2O2 leads to the enhancement of ions that can undergo ion vibration in the system and leads to the enhancement of microwave thermal performance.

[0136] (3) In vitro microwave sensitization performance test 3:

[0137] 1,3-Diphenylbenzofuran (DPBF) is a commonly used singlet oxygen ( 1 O2) detection probe, DPBF itself has an ultraviolet absorption peak at 420nm, and when singlet oxygen exists in the solution, singlet oxygen oxidizes DPBF, and the absorbance of the absorption peak at 420nm will decay, and this decay is proportional to the content of singlet oxygen in the solution. Therefore, by analyzing the changes in the ultraviolet absorption value of DPBF, the microwave dynamic sensitization effect of Co-Ti MOFs and CoO / TiO2@C can be indirectly evaluated.

[0138] In the experiment, the Co-Ti MOFs in Example 1 and the CoO / TiO2@C in Example 13 were first quantitatively processed. The two materials of the same mass were dispersed in deionized water, 8 μL of DPBF solution (1 mg / mL, dissolved in DMSO) was added under light-proof conditions, and then stirred in the dark for 5 min. The mixed solution of DPBF and the two materials was exposed to microwave irradiation at fixed time intervals under dark conditions, and the output power of the microwave was 2 W. After irradiation for different times, the ultraviolet absorption value was detected using an ultraviolet-visible spectrophotometer in the wavelength range of 350nm to 700nm.

[0139] according to Fig.17It can be seen that the DPBF absorbance of the blank control group did not decrease significantly, while Co-Ti MOFs+H2O2 and CoO / TiO2@C+H2O2 showed different degrees of decrease in DPBF ultraviolet absorption value within a certain range after microwave irradiation. Under the same microwave output power and the same microwave irradiation time, the decrease in DPBF ultraviolet absorption value of the CoO / TiO2@C+H2O2 group was more obvious than that of the Co-Ti MOFs nanosheets group. Co-Ti MOFs (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 1 to 5, Ti MOFs in Comparative Example 1, Co MOFs in Comparative Example 3, CoO / TiO2@C (Co:Ti=1:4, 1:2, 1:1, 2:1, 4:1) in Examples 9 to 13, TiO2@C in Comparative Example 2, and CoO@C in Comparative Example 4 were dispersed in deionized water to obtain a homogeneous solution with a concentration of 100 μg / mL as the experimental group. A separate deionized water group was set as the control group. In addition, H2O2 was added to both the experimental group and the control group and quantified to 100 μM.

[0140] according to Fig.18 , 19 It can be seen that after 5 minutes of microwave irradiation, the relative concentration of DPBF in the CoO / TiO2@C (Co:Ti=4:1)+H2O2 group reached 25.7%, while the relative concentration of DPBF in the Co-Ti MOFs (Co:Ti=4:1)+H2O2 group with the same metal doping ratio was 63.35%, and the relative concentration of DPBF in the Co-Ti MOFs (Co:Ti=1:4)+H2O2 group with the best sensitization performance was 34.1%. The above results show that the microwave dynamic sensitization efficiency of CoO / TiO2@C is significantly better than that of Co-Ti MOFs, and it has the potential to become an excellent microwave sensitizer. This may be due to the increase in oxygen vacancies in the sample and the formation of heterojunctions caused by the doping of cobalt metal, which leads to easier electronic transitions, showing more active catalytic sites, which is more conducive to the separation of electron-hole pairs, thereby generating more ROS under microwave irradiation. The above results show that the prepared CoO / TiO2@C is an efficient microwave sensitizer of titanium-based metal organic framework-derived materials.

[0141] Application Example 3

[0142] In vitro tumor cell uptake behavior test

[0143] The CoO / TiO2@C@PEG (Co:Ti=4:1) in Example 15 was modified with rhodamine B (Rh B). The HepG2 cells digested with trypsin were resuspended in new complete culture medium and cultured at 8×10 3The cells were inoculated in a confocal culture dish at a density of 1000 cells / dish, and cultured in an incubator overnight to allow the cells to adhere to the wall and grow. After the incubation, the old culture medium was discarded, and the complete culture medium containing the CoO / TiO2@C@PEG nanosheets (100 μg / mL) in Example 15 labeled with the Rh B fluorescent group was co-incubated with HepG2 cells for 0 h, 2 h, and 6 h, respectively. Washed three times with PBS to remove the CoO / TiO2@C@PEG nanosheets that were not internalized by the cells. Hoechst33342 was co-incubated with HepG2 cells in the dark for 30 minutes to stain the cell nuclei. After the incubation, the cells were fixed at 4°C for 30 minutes with pre-cooled 4% paraformaldehyde. After washing three times with PBS, laser scanning confocal microscope images were taken with a laser confocal microscope, and the cells were observed using a 60x objective. Among them, the cell nuclei stained with Hoechst 33342 showed blue fluorescence, and the Rh B modified Co-Ti MOFs@PEG nanosheets showed red fluorescence.

[0144] from Fig. 20 It can be seen that within a certain range, the fluorescence intensity first increases and then decreases. At 0.5h of co-incubation, CoO / TiO2@C@PEG nanosheets have been enriched in HepG2 cells and emit red fluorescence. At 3h, it can be observed that it has the brightest red fluorescence, and at 4h, the fluorescence weakens. This shows that CoO / TiO2@C@PEG nanoparticles can be effectively taken up by HepG2 cells and the maximum uptake is reached at 3h, which lays the foundation for further microwave hyperthermia combined with microwave dynamic therapy.

[0145] Application Example 4

[0146] (1) Biosafety Test 1

[0147] The Co-Ti MOFs@PEG (Co:Ti=4:1) in Example 14 and the CoO / TiO2@C@PEG (Co:Ti=4:1) in Example 15 were prepared into a 2 mg / mL high concentration buffer solution using PBS as a solvent, and then diluted with culture medium to prepare experimental concentrations of 0, 10, 20, 40, 60, 80, and 100 μg / mL, respectively, and co-cultured with HepG2 cells and L-02 cells for 12 h, respectively.

[0148] The Co-Ti MOFs@PEG in Example 14 and the CoO / TiO2@C@PEG in Example 15 were prepared into a 2 mg / mL high concentration buffer solution using PBS as a solvent, and then diluted with complete culture medium to prepare experimental concentrations of 0, 10, 20, 40, 60, 80, and 100 μg / mL, respectively. H2O2 was added to ensure that 100 μM H2O2 was present in each experimental concentration, and then co-cultured with HepG2 cells and L-02 cells for 12 h, respectively.

[0149] The results are as follows Fig.21 As shown, it can be seen that the cells have good activity at all experimental concentrations of the present invention. Even at a concentration of 100 μg / mL, the survival rate of HepG2 cells and L-02 cells is still above 85%. The results show that Co-TiMOFs@PEG, CoO / TiO2@C@PEG and CoO / TiO2@C@PEG+100μM H2O2 have low dark toxicity to HepG2 cells and L-02 cells, and have good biosafety; 100μg / mL Co-Ti MOFs@PEG nanosheets, CoO / TiO2@C@PEG and CoO / TiO2@C@PEG+100μM H2O2 are safe doses that can be further used in vivo.

[0150] (2) Biosafety Test 2

[0151] Co-Ti MOFs@PEG (Co:Ti=4:1) of Example 14 and CoO / TiO2@C@PEG (Co:Ti=4:1) of Example 15 with different concentrations (0, 20, 40, 60, 80, 100 μg / mL) were incubated with HepG2 cells for 3 h, and then microwave irradiated with an output power of 2 W and an irradiation time of 5 min.

[0152] The results are as follows Fig. 22 As shown in the figure, it can be seen that with the increase of material concentration, the survival rate of HepG2 cells gradually decreases. When the concentration of CoO / TiO2@C@PEG+100μM H2O2 is 100μg / mL, the survival rate of HepG2 cells under microwave irradiation is only 28.6%. Under the same conditions, when the concentration of Co-Ti MOFs@PEG is 100μg / mL, the survival rate of HepG2 cells under microwave irradiation is 41.8%. This may be because CoO / TiO2@C@PEG+100μM H2O2 can produce more reactive oxygen species under microwave irradiation, has better microwave power therapy effect, and has a more obvious killing effect on cells. The above results show that both Co-Ti MOFs@PEG and CoO / TiO2@C@PEG can enhance microwave sensitization performance at the cellular level, among which CoO / TiO2@C@PEG nanosheets show better microwave sensitization performance and better cancer cell killing effect, which can be further used for in vivo microwave therapy.

[0153] Application Example 5

[0154] Fluorescence image test:

[0155] HepG2 cells were co-incubated with 2,7-dichlorofluorescein diacetate (DCFH-DA) ROS probe for staining. The trypsin-digested HepG2 cells were resuspended in new complete culture medium at a concentration of 3 × 10 cells / well. 4 The cells were inoculated in a 6-well plate at a density of 1.5 and cultured overnight in an incubator at 37°C and 5% CO2. After observing the cells adhered to the wall under a microscope, the old culture medium was discarded, and the complete culture medium containing Co-Ti MOFs@PEG (Co:Ti=4:1) nanosheets and CoO / TiO2@C@PEG (Co:Ti=4:1) nanoparticles (100μg / mL) was added to each well, and the cells were incubated in an incubator at 37°C and 5% CO2 for 2h. After the incubation, the Co-Ti MOFs@PEG nanosheets and CoO / TiO2@C@PEG nanoparticles that did not enter the cells were washed with PBS, and the cells were recorded as experimental group 1, and the group incubated with pure PBS was recorded as control group 1. The above operation was repeated, and 100μM H2O2 was added to each well, and the cells were recorded as experimental group 2, and the group incubated with 100μM H2O2 was recorded as control group 2. Fresh complete culture medium containing DCFH-DA was added to each well, and the cells were incubated for 40min. Then the microwave ablation needle was vertically inserted below the liquid surface of each well, and the cells were treated or not treated with microwave irradiation (output power of 2W, irradiation time of 5min). Then the cells were incubated in the dark for 1h, and then fixed with pre-cooled 4% paraformaldehyde. Finally, an inverted fluorescence microscope was used to observe the DCF green fluorescence to detect the generation of reactive oxygen species in the cells, using a 20x microscope for observation and an excitation wavelength of 488nm. The same steps were used to detect the generation of reactive oxygen species in cells under microwave irradiation of Co-Ti MOFs@PEG.

[0156] The results are as follows Fig.23As shown in the figure, it can be seen that the 2,7-dichlorofluorescein diacetate (DCFH-DA) ROS probe was co-incubated with HepG2 cells to verify the generation of intracellular ROS in different groups. DCFH-DA is converted into DCFH in cells. When reactive oxygen species are generated in cells, it will be oxidized into DCF with bright green color. The level of intracellular ROS can be indirectly reflected by the observed green fluorescence intensity. As can be seen from the figure, the blank control group (Control group, H2O2 group) behaved normally, and no green fluorescence was generated even under microwave irradiation. Both the Co-Ti MOFs@PEG group and the CoO / TiO2@C@PEG group did not produce green fluorescence without microwave irradiation. Weak green fluorescence was visible after 5 minutes of microwave irradiation, indicating that the blank control group did not produce ROS at the cellular level, while the ROS generation at the cellular level was very small under microwave irradiation of Co-Ti MOFs@PEG and CoO / TiO2@C@PEG alone. The Co-Ti MOFs@PEG+H2O2 group and the CoO / TiO2@C@PEG+H2O2 group showed green fluorescence. After the Co-Ti MOFs@PEG+H2O2 group and the CoO / TiO2@C@PEG+H2O2 group were co-incubated with HepG2 cells and then microwave irradiated, the green fluorescence on the cells was significantly enhanced, indicating that ROS increased significantly at the cellular level. This result is consistent with the results of DPBF in vitro microwave power detection. The reason why the CoO / TiO2@C@PEG+H2O2+MW group produced more ROS may be that CoO / TiO2@C has a smaller bandgap than Co-Ti MOFs and contains more oxygen vacancies on the surface. At the same time, the formation of heterojunctions is conducive to the transition of electrons between interfaces, which is conducive to the generation of more reactive oxygen species under microwave induction, showing enhanced microwave power sensitization performance.

[0157] According to application examples 3 to 5, Co-Ti MOFs@PEG and CoO / TiO2@C@PEG nanoparticles are potential microwave dynamic sensitizers, and CoO / TiO2@C@PEG nanoparticles have a more excellent microwave dynamic sensitization effect, which can be further used for microwave treatment of liver cancer in vivo. These results confirm that CoO / TiO2@C@PEG can be used as a tumor microwave treatment sensitizer and show good effects.

[0158] In summary, the microwave sensitizer of the present invention has biosafety, can be used for fluorescence imaging, and is helpful for real-time observation in microwave ablation; and the microwave sensitizer of the present invention utilizes a heterojunction structure to enhance the microwave thermal conversion efficiency, and combines microwave dynamic sensitization and microwave-excited chemical dynamic sensitization to achieve absorption enhancement under low-frequency microwaves.

[0159] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate, characterized in that: The heterojunction-porous composite material of the bimetallic oxide and the carbon layer substrate is prepared by carbonizing the porous bimetallic-organic framework material at 400-900° C. in a protective atmosphere; The porous bimetallic-organic framework material is an X metal ion doped Y metal-organic framework material, wherein the X metal and the Y metal both include one or more of rare earth metals, alkaline earth metals, main group metals, and transition element metals, and the X metal and the Y metal are different metals.

2. The heterojunction-porous composite material of bimetallic oxide and carbon layer substrate according to claim 1, characterized in that: The porous bimetallic-organic framework material is prepared by adding ligand molecules and Y metal compounds into a mixed organic solution, reacting at 50-130° C. for 1-24 hours, adding X metal doping salt, and reacting at 135-200° C. for 12-48 hours.

3. The heterojunction-porous composite material of bimetallic oxide and carbon layer substrate according to claim 1, characterized in that: The molar ratio of X metal doping salt to Y metal compound in the porous bimetallic-organic framework material is 1:(0.1-10).

4. The heterojunction-porous composite material of bimetallic oxide and carbon layer substrate according to claim 1, characterized in that: The porous bimetal-organic framework material is in the form of nanosheets, with an average size of 100 to 1000 nm and a thickness of 10 to 50 nm.

5. A heterojunction-porous composite material CoO / TiO2@C composited with a bimetallic oxide and a carbon layer substrate, characterized in that: It is prepared by carbonizing the porous bimetallic-organic framework material Co / TiMOFs at 400-900° C. in an inert gas.

6. A heterojunction-porous composite material of a double metal oxide of a surface-modified polymer and a carbon layer substrate, characterized in that: The polymer is modified on the surface of the heterojunction-porous composite material of the double metal oxide and the carbon layer substrate as described in any one of claims 1 to 4.

7. A heterojunction-porous composite material of a double metal oxide coupled with a tumor targeting molecule and a carbon layer substrate, characterized in that: Tumor targeting molecules are coupled to the surface of the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate as described in any one of claims 1 to 4, and / or the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate of a surface-modified polymer as described in claim 6.

8. A heterojunction-porous composite material of a bimetallic oxide loaded with an anti-tumor drug and a carbon layer substrate, characterized in that: The anti-tumor drug is loaded on the surface of the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate as described in any one of claims 1 to 4, and / or the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate with a surface-modified polymer as described in claim 6, and / or the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate coupled with a tumor targeting molecule as described in claim 7.

9. A heterojunction-porous composite material of a bimetallic oxide loaded with an immune activator and a carbon layer substrate, characterized in that: The surface of the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate as described in any one of claims 1 to 4, and / or the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate of a surface-modified polymer as described in claim 6, and / or the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate coupled with a tumor targeting molecule as described in claim 7, and / or the heterojunction-porous composite material of a bimetallic oxide and a carbon layer substrate loaded with an anti-tumor drug as described in claim 8 is loaded with an immune activator.

10. A microwave sensitizer, characterized in that: It includes one or more of the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate as described in any one of claims 1 to 4, the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate of a surface-modified polymer as described in claim 6, the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate coupled with a tumor targeting molecule as described in claim 7, the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate loaded with an anti-tumor drug as described in claim 8, and the heterojunction-porous composite material of a double metal oxide and a carbon layer substrate loaded with an immune activator as described in claim 9.